In vivo microbiological evaluation of the effect of biomechanical preparation of root canals using different irrigating solutions - Tanomaru Filho, Mario [UNESP]; Yamashita, José Carlos [UNESP]; Leonardo, Mario Roberto; Silva, Léa Assed Bezerra da; Tanomaru, Juliane Maria Guerreiro [UNESP]; Ito, Izabel Yoko (FapUNIFESP (SciELO), 2006)
The aim of this study was to evaluate the antimicrobial effect of biomechanical preparation using different irrigating solutions. Seventy-eight root canals from premolars of four dogs were used. After experimental induction of periapical lesions, the root canals were prepared using the following solutions for irrigation: Group 1) 2.5% sodium hypochlorite (NaOCl); Group 2) 2% chlorhexidine (CHX); Group 3) saline solution and Group 4) control group with no biomechanical preparation. The microbiological evaluation of the root canals was performed by counting the colony forming units (CFUs) using different culture mediums. Two absorbent paper cones were used in each root canal in order to collect the microbiological samples before, and thirty days after the biomechanical preparation. The culture plates were incubated in aerobic, anaerobic and microaerophilic environment. Statistical evaluation was carried out using analysis of variance, Tukey and Student tests. The results demonstrated that there was reduction in the number of microorganisms in the NaOCl and CHX groups (p<0.05). There was greater effectiveness in the chlorhexidine group. The group that used saline solution and the control group presented an increased number of microorganisms. It can be concluded that the use of antimicrobial irrigating solutions during biomechanical preparation promotes the reduction of endodontic microbiota. However, a considerable number of microorganisms were still observed.
Keywords: Chlorhexidine; Endodontics; Microbiology; Sodium hypochlorite